Model Pemasaran Biogas Dalam Tabung Berbasis Modal Sosial Pada Kelompok Masyarakat Guna Meningkatkan PADes - Djasuli, Mohammad; Lutfia, Citra; Harwida, Gita Arasy; Niswah, Nurin (Society : Jurnal Pengabdian Masyarakat, 2024)
In order to increase the Village's Original Income (PADes), this study proposes to create a model of biogas commercialization in tubes based on social capital in environmental organizations. The marketing of biogas products is based on the principles of social capital, which combines aspects of sustainability, efficiency, and community empowerment. This study assessed the efficiency of the social capital-based biogas marketing model in increasing the income and welfare of community groups through surveys, interviews, and data analysis. To support the growth of biogas at the village level, local governments, non-profit groups, and industry players are requested to use the findings of this study as a guide in making more effective marketing policies and tactics. Thus, the implementation of these strategies is expected to positively contribute to economic and environmental empowerment at the village level while increasing Village Original Revenue as a step towards sustainable development.